Russia's Economy Signs of Progress and Retreat on the Transitional Road - Wolf, Charles Jr (RAND Corporation, 2006)
Sixteen years after the Soviet Union's demise, the Russian economy can still be appropriately characterized as transitional. The authors shed light on ambiguities surrounding this status through an exploration of four questions related to issues of interest to government decisionmakers.